2008
DOI: 10.1186/1746-6148-4-37
|View full text |Cite
|
Sign up to set email alerts
|

Expressed sequence tags (ESTs) from immune tissues of turbot (Scophthalmus maximus) challenged with pathogens

Abstract: Background: The turbot (Scophthalmus maximus; Scophthalmidae; Pleuronectiformes) is a flatfish species of great relevance for marine aquaculture in Europe. In contrast to other cultured flatfish, very few genomic resources are available in this species. Aeromonas salmonicida and Philasterides dicentrarchi are two pathogens that affect turbot culture causing serious economic losses to the turbot industry. Little is known about the molecular mechanisms for disease resistance and hostpathogen interactions in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
3
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 56 publications
1
55
3
1
Order By: Relevance
“…In both species the most represented biological functions according to the Gene Ontology classification were immune system, cell communication, metabolism and transport. Although we classified the biological process of transferrin as transport, a glycoprotein responsible for the transport and delivery of iron to cells, it is also related to the innate immune response of fish because of the importance of free iron for bacterial infections (Stafford and Belosevic, 2003;Pardo et al, 2008). The transferrin gene, together with other genes that we found in liver such as apolipoprotein and fibrinogen, has been shown to be regulated by estrogens in females (Pinto et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both species the most represented biological functions according to the Gene Ontology classification were immune system, cell communication, metabolism and transport. Although we classified the biological process of transferrin as transport, a glycoprotein responsible for the transport and delivery of iron to cells, it is also related to the innate immune response of fish because of the importance of free iron for bacterial infections (Stafford and Belosevic, 2003;Pardo et al, 2008). The transferrin gene, together with other genes that we found in liver such as apolipoprotein and fibrinogen, has been shown to be regulated by estrogens in females (Pinto et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In turbot, despite large collections of immune-related genes being available (Pardo et al, 2008;Park et al, 2009) and an oligo-microarray having been designed and calibrated based on this database (Millán et al, 2010), no gonad-related expressed genes have been reported to date. In this work we used the cDNA-AFLP methodology to comparatively analyze gene expression in mature gonads, liver and brain of males and females.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several cDNA libraries of turbot immune-relevant tissues have been constructed and more than one thousand genes were identified (Meng et al 2008;Pardo et al 2008;Park et al 2009), while little is known about the detailed functions formation of these genes. The establishment of suitable cell lines could help to analyze the function of these important immune genes.…”
Section: Introductionmentioning
confidence: 99%
“…Oncorhynchus mykiss (Govoroun et al 2006;Sánchez et al 2009), Atlantic salmon Salmo salar Hagen-Larsen et al 2005;Hayes et al 2007), common carp Cyprinus carpio (González et al 2007), catfish Ictalurus punctatus and I. furcatus Wang et al 2010), Nile tilapia Oreochromis niloticus , cod Gadus morhua (Johansen et al 2011), European seabass Dicentrarchus labrax (Chini et al 2006;Louro et al 2010), Asian seabass Lates calcarifer (Xia and Yue 2010), Atlantic halibut Hippoglossus hippoglossus (Douglas et al 2007), Senegalese sole Solea senegalensis (Cerdà et al 2008), turbot Psetta maxima (Pardo et al 2008), and half-smooth tongue sole Cynoglossus semilaevi . For the gilthead seabream, an initial EST project yielded approximately 1,400 sequences, 810 of which were derived from a mixed juvenile and yolk sac larvae cDNA library and the other 584 sequences were derived from an adult liver cDNA library (Sarropoulou et al 2005a).…”
Section: Introductionmentioning
confidence: 99%